2021
DOI: 10.48550/arxiv.2107.02319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring Deep Learning Methods for Real-Time Surgical Instrument Segmentation in Laparoscopy

Abstract: Minimally Invasive Surgery (MIS) is a surgical intervention used to examine the organs inside the abdomen and has been widely used due to its effectiveness over open surgery. Due to the hardware improvements such as high definition cameras, this procedure has significantly improved and new software methods have demonstrated potential for computer-assisted procedures. However, there exists challenges and requirement to improve detection and tracking of the position of the instruments during these surgical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Best results were reported by the U-Net based solutions. Jha et al (2021b) tested a dual decoder attention network (DDANet) and nine different methods on the ROBUST-MIS dataset. They reported that the DDANet architecture provided the highest metric and best real-time performance over the other methods.…”
Section: Tool Segmentation Researchmentioning
confidence: 99%
“…Best results were reported by the U-Net based solutions. Jha et al (2021b) tested a dual decoder attention network (DDANet) and nine different methods on the ROBUST-MIS dataset. They reported that the DDANet architecture provided the highest metric and best real-time performance over the other methods.…”
Section: Tool Segmentation Researchmentioning
confidence: 99%